PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN EKONOMI - Khalimi, Soleh; Sulistyarini, Sulistyarini; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to determine the use of video learning as the media in increasing student activity and student learning outcomes. The method used in this research was descriptive method with classroom action research as the form of research. The subjects of this study were Senior High School 10 Pontianak class X, which was 35 students. The data collection technique was direct observation with two observation sheets, they were student learning activities and educator ability observation sheets, as the tool of the data collection. The indicators seen from learning activities were (1) visual activities (2) oral activities (3) listening activities (4) writing activities (5) mental activities and (5) emotional activities. It can be concluded that using video learning as the media can improve student activity and learning outcomes in Senior High School 10 Pontianak class X.Â Keywords: Media, Learning Activity, Students ScoreÂ